Detection of stx1 and stx2 and subtyping of Shiga toxin-producing Escherichia coli using asymmetric PCR combined with lateral flow immunoassay. (August 2021) - Shan, Shan; Huang, Yanmei; Huang, Zhaohong; Long, Zhonger; Liu, Chengwei; Zhao, Xuelong; Xing, Keyu; Xiao, Xiaoyue; Liu, Jintao; Huang, Yunhong; Lai, Weihua; Liu, Daofeng
Abstract: Shiga toxin-producing Escherichia coli (STEC) is known as a kind of foodborne pathogens that can produce Shiga toxin type1, type 2, or both, encoded by stx1 and stx2 genes, respectively. Rapid and accurate detection of STEC and stx1 / stx2 subtyping assay in food and environment is essential for foodborne outbreak investigation. In this study, a method for the accurate and rapid subtyping of STEC single colony using asymmetric polymerase chain reaction (asPCR) combined with lateral flow immunoassay (LFIA) was established. AsPCR was conducted using biotinylated stx1 and digoxin-labeled stx2 primers to obtain several single stranded DNA amplicons labeled with biotin or/and digoxin. Subsequently, these amplicons were tagged with specific probes labeled with carboxylate-modified red polystyrene microspheres using sequential hybridization. Finally, STEC with different Shiga toxin gene types could be distinguished depending on the appearance of different test lines on an LFIA strip. Thus, the STEC single colony could be identified and subtyped accurately and conveniently using this method. This method showed high specificity. Twenty-four strains of STEC in milk were detected and subtyped using our method, which combines asPCR with LFIA.